2022
DOI: 10.21203/rs.3.rs-1721620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Burden of Non-Communicable Diseases among Hospitalized HIV Positive Patients at Lira Regional Referral Hospital, Northern Uganda: Retrospective Chart Review 2016-2020

Abstract: Background: Non-communicable diseases(NCDs) are increasing rapidly in sub-Sahara Africa including Uganda. Knowledge of the effect of long-term antiretroviral therapy(ART) and emergence of NCDs on hospital utilization remain scant. This study aimed to assess the burden of major NCDs and predictors of mortality among hospitalized HIV positive patients in the medical wards at Lira regional referral hospital in Northern Uganda.Method: We conducted a retrospective cross-sectional chart review of hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The escalation levels of adults living with HIV and hypertension is concerning because it is associated with increased morbidity and mortality and has shown upward trends in the recent years [6,15,16]. However, it is reported that the use of ART medications improves the quality of life and life expectancy of PLWHA in Northern Uganda, though exposure to the effects of aging, including the influence of environmental risk factors, was known to act in the general population and contribute to the occurrence of NCDs such as hypertension, heart attacks, and stroke, chronic renal diseases, and osteoporotic fractures [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The escalation levels of adults living with HIV and hypertension is concerning because it is associated with increased morbidity and mortality and has shown upward trends in the recent years [6,15,16]. However, it is reported that the use of ART medications improves the quality of life and life expectancy of PLWHA in Northern Uganda, though exposure to the effects of aging, including the influence of environmental risk factors, was known to act in the general population and contribute to the occurrence of NCDs such as hypertension, heart attacks, and stroke, chronic renal diseases, and osteoporotic fractures [17,18].…”
Section: Introductionmentioning
confidence: 99%